ETHICAL DILEMMAS IN NEUROMARKETING: NAVIGATING PERSUASION, CONSUMER AUTONOMY, AND EMERGING TECHNOLOGIES - Muhamad Stiadi; Luana Sasabone; Deisye Supit; Cut Ita Erliana; Dahlan Abdullah (ADISAM Publisher, 2024)
Neuromarketing is a rapidly growing field that uses neuroscience to understand consumer behavior and improve marketing effectiveness. This article explores the complex ethical implications of neuromarketing practices, especially regarding persuasive influence on consumer autonomy and the use of emerging technologies. First, we investigate advances in neurotechnology, such as fMRI, EEG, and brain-computer interfaces (BCIs), that enable a deeper understanding of consumer preferences. The challenge is enforcing this technology's ethical use and protecting individual privacy. Second, we discuss